PENGARUH PENGAWASAN DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK MADYA PALEMBANG - Sahyuni . (JURNAL KOMPETITIF, 2013)
Research Methode in this research was causality methode. The population in this research are 81 (eighty one) employees at Kantor Pelayanan Pajak Madya Palembang. The number of sample are 50 (fifety) employees at Kantor Pelayanan Pajak Madya Palembang. Data collecting is obtained by conducted answer questionnaires. The analysis model used is multiple regression linier. The variable used independent variables those are : supervision (X1), discipline (X2) and dependent variable that is : job performance (Y) of Kantor Pelayanan Pajak Madya PalembangÃ¢â‚¬â„¢s employee. According to the result the simultaneously independent variables (supervision and discipline) had significant effect on dependent variable with sig. F value = 0.000 < 0.05, and partially independent variables (supervision and discipline) had significant effect on dependent variable (job performance) of Kantor Pelayanan Pajak Madya PalembangÃ¢â‚¬â„¢s employee. Independent variables (supervision and discipline) by simultaneouse Correlation was 0.976 (97.6%). Independent variables (supervision and discipline) had simultaneouse affect to dependent variable (job performance) with R2 value = 0.952 (95.2%) while the other 4.8% is explained by other variables not included in this study.Ã‚Â Keywords : Supervision, Discipline, Job PerformanceÃ‚Â